Evaluating package delivery crowdsourcing using location traces in different population densities. (September 2022) - Arditi, Ayelet; Toch, Eran
Abstract: Crowdsourcing package delivery is an emerging business activity that utilizes people's existing travel for delivering packages and mail. While crowdsourcing can address the growing need for faster and cheaper package delivery without deploying the system, it is unclear which types of local crowdsourcing can be effective and perform in urban, suburban, and rural areas. This study suggests a method for simulating package delivery architectures using anonymized mobile location traces, comparing prominent architectures, and elevating the success rates, duration periods, and other measures in different geographical locales. Based on a sample of 1.8 million cellular phone users in Israel, we show that both systems have performance challenges in areas with low population density. Our analysis also indicates that multi-hop architectures allow couriers to transfer packages to their destination by leaving them at intermediate stop points until the next courier picks them up, outperforming one-hop architectures, in which packets can be transferred between origin and destination stop points by one courier. We conclude the paper by discussing how mobility-based simulation methods can be used to assess the performance of mobile crowdsourcing systems before they are built. Highlights: We have used anonymized location traces to simulate crowdsourced package delivery systems We have analyzed the performance of crowdsourcing architectures under different participation rates and population densities Areas with low population density are harder to serve, and require a larger number of locker sites for a similar level of service Performance drops to unattainable levels in areas with low population density in existing transportation volume conditions